Un/doing gender stereotypes in digital technology journalism - Clark, Vanessa (Centre for Film and Media Studies, 2023)
This creative media project and essay explore how the editorial brief impacts the creation of gender stereotyped digital technology entrepreneurs in digital technology journalism in South Africa. A second objective is to explore how journalists can create alternative, nongender stereotyped stories about digital technology entrepreneurs in South Africa. The qualitative study's points of departure are the under- and misrepresentation of women in the media and the gendered stereotyping of digital technology entrepreneurs. Further, the researcher's professional experience as a digital technology journalist suggested the editorial brief, as the primary and most salient point of contact between a freelance journalist, their editor and the publication, would be a critical area of study. The researcher creates three pieces of media (a feature article, three book chapters and a podcast) about women digital technology entrepreneurs based on semi-structured interviews. She then uses auto-ethnographic, critical reflection to compare and contrast the productions with her typical experience as a journalist, and considers the broader implications for digital technology business journalism, paying specific attention to editorial authority and ethical considerations. The work establishes that there are actions journalists and editors can take today to avoid gender stereotyping entrepreneurs. The results support the thinking that the editorial briefs should not be considered neutral or inert and so their impact should be carefully considered by editors and journalists. The findings, although limited by the size and nature of the project, could contribute to further research into the media production of digital technology business journalism, and the role of production factors in producing more feminist journalism.